Perceived Marketing System Effectiveness by Pineapple Growers in Tripura - Priyanka Roy; Souvik Ghosh (Indian Journal of Extension Education, 2022)
Pineapple, an important cash crop of Tripura providing the major source of farm livelihood, has been facing marketing challenges. Present study was conducted during January-June 2020 to assess farmers’ perceptions towards marketing system effectiveness of pineapple that included a random sample of 80 farmers. Marketing system effectiveness was measured on different aspects of pineapple marketing based on farmers’ perceptions on 5-point continuum. Higher mean perception scores (>4.0) were obtained for two aspects viz., grading & quality checking, and direct selling of produce. Contrastingly, lower perception scores (<2.0) were found for many aspects like inadequate transportation system, profit and price determination by middleman, fluctuating marketing price, non-availability of up-to-date market information, excessive time to disposing produce, government marketing channel & auction, and inability of small-scale farmers to bringing produce to market. Overall marketing system effectiveness was found 47 per cent. Attributes of farmers were having significant correlation with it; out of which family size, use of personal cosmopolite information sources, mass media use and knowledge level showed significant relationship in multiple regression model. Therefore, to improve pineapple marketing system effectiveness, extension and advisory services need to undertake capacity building measures of the pineapple growers.